An enriched environment ameliorates the reduction of parvalbumin-positive interneurons in the medial prefrontal cortex caused by maternal separation early in life - Irie, Kanako; Ohta, Ken-ichi; Ujihara, Hidetoshi; Araki, Chihiro; Honda, Kodai; Suzuki, Shingo; Warita, Katsuhiko; Otabi, Hikari; Kumei, Haruki; Nakamura, Shinji; Koyano, Kosuke; Miki, Takanori; et al. (Frontiers in Neuroscience, 2024)
Early child maltreatment, such as child abuse and neglect, is well known to affect the development of social skills. However, the mechanisms by which such an adverse environment interrupts the development of social skills remain unelucidated. Identifying the period and brain regions that are susceptible to adverse environments can lead to appropriate developmental care later in life. We recently reported an excitatory/inhibitory imbalance and low activity during social behavior in the medial prefrontal cortex (mPFC) of the maternal separation (MS) animal model of early life neglect after maturation. Based on these results, in the present study, we investigated how MS disturbs factors related to excitatory and inhibitory neurons in the mPFC until the critical period of mPFC development. Additionally, we evaluated whether the effects of MS could be recovered in an enriched environment after MS exposure. Rat pups were separated from their dams on postnatal days (PDs) 2–20 (twice daily, 3 h each) and compared with the mother-reared control (MRC) group. Gene expression analysis revealed that various factors related to excitatory and inhibitory neurons were transiently disturbed in the mPFC during MS. A similar tendency was found in the sensory cortex; however, decreased parvalbumin (PV) expression persisted until PD 35 only in the mPFC. Moreover, the number of PV+ interneurons decreased in the ventromedial prefrontal cortex (vmPFC) on PD 35 in the MS group. Additionally, perineural net formation surrounding PV+ interneurons, which is an indicator of maturity and critical period closure, was unchanged, indicating that the decreased PV+ interneurons were not simply attributable to developmental delay. This reduction of PV+ interneurons improved to the level observed in the MRC group by the enriched environment from PD 21 after the MS period. These results suggest that an early adverse environment disturbs the development of the mPFC but that these abnormalities allow room for recovery depending on the subsequent environment. Considering that PV+ interneurons in the mPFC play an important role in social skills such as empathy, an early rearing environment is likely a very important factor in the subsequent acquisition of social skills.